Formal models, languages and applications - Subramanian, K. G; Rangarajan, K; Mukund, M (Series in machine perception and artificial intelligence, 2006)
A collection of articles by leading experts in theoretical computer science, this volume commemorates the 75th birthday of Professor Rani Siromoney, one of the pioneers in the field in India. The articles span the vast range of areas that Professor Siromoney has worked in or influenced, including grammar systems, picture languages and new models of computation.